Study on the Effects of Mineral Fertilizers on Growth, Fruit Yield and Nutrient Uptake of Tomato (Lycopersicon lycopersicum Mill) in Ogbomoso and Mokwa, Nigeria - Tswanya, M. N.; Olaniyi, J. O.; Ahmed, M. (Recent Progress in Plant and Soil Research Vol. 3, 2021)
Field experiments were conducted at the Teaching and Research Farm, Ladoke Akintola University of Technology, Ogbomoso and Niger State College of Agriculture, Mokwa in 2013 cropping season to examine the effects of mineral fertilizers on growth, fruit yield and nutrient uptake of tomato. Tomato cultivation in the country has improved from the traditional intercropping system with major staple crops to a much more commercially oriented system. The treatments consisted of 3 mineral fertilizer types at 3 rates each and their combinations were used, namely: N (0, 30 and 60 in kg N ha-1), P (0, 25 and 50 kg P2O5ha-1), K (0, 16.5 and 33 kg K2O ha-1). The treatments were laid out in a Randomized Complete Block Design (RCBD), replicated 3 times. Data were collected on plant height, number of leaves per plant, number of flowers per plant, number of fruits per plant, total fruit yield and nutrient uptake. The determination of leaf phytochemical contents were randomly selected per plot and analyzed for nutrient uptake such as N, P, K, Ca and Mg contents. Data were analyzed using analysis of variance (ANOVA) SAS package and treatment means were separated using Duncan Multiple Range Test (DMRT) at 5% probability level. The objective of the study was to determine mineral fertilizer combinations that will increase the nutrient uptake for optimum tomato performance. External input of mineral fertilizer improved tomato yield and nutrient uptake of tomato. Application of 60 kg N ha-1 + 50 kg P2O5 ha-1 + 33 kg K2O ha-1 gave the highest fruit yield (27.81 t ha-1) while control plot had the least (9.96 t ha-1). Nutrient uptake (P, K) was best at fertilizer rates of 60 kg N ha-1 + 50 kg P2O5 ha-1 + 33 kg K2O ha-1. In conclusion, external input of mineral fertilizer is necessary to improve tomato yield and nutrient uptake contents. Plants fertilized with 60 kg N ha-1 + 50 kg P2O5 ha-1 + 33 kg K2O ha-1 responded better than other rates and therefore can be recommended for farmers to increase production within the study areas.